Pelatihan Strategi Pemasaran untuk Usaha Mikro Kecil Menengah Binaan Kantor Walikota Jakarta Utara - Setianingsih, Rita Eka; Sandra, Amelia; Arfianti, Rizka Indri (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2024)
The Covid-19 pandemic has had a significant impact on the government and society. Many business actors have experienced a decrease in sales turnover. This pandemic requires MSME owners to be able to think strategically and dynamically to maintain the business that has been built. MSMEs face a variety of challenges, including ideas, administration, marketing, and money. Administration and marketing concerns are still the key challenges in growing a firm because understanding in these areas is still relatively poor. A good strategy is needed to keep them afloat and increase their revenue turnover. The Indonesian government has tried to make several policies to strengthen MSMEs during the Covid-19 pandemic. For example, During the Covid-19 epidemic, the provision of social aid, tax incentives, and working capital growth all have an impact on MSMEs' development. Marketing strategy is one technique to gain a sustained competitive edge, whether for a company that manufactures goods or services. There are several marketing strategies that can be done to overcome the problems that occur. MSME players are able to survive the pandemic by maximizing sales in the online market. Empowering MSME players in the products that are most needed during the pandemic is necessary for empowering the community of MSME players to test the online market. MSMEs must strive to adopt various digital technologies to overcome this crisis. For this reason, this training is expected to help MSME owners assisted by the North Jakarta Mayor's Office develop and improve their businesses.